Enzymatic variability among venoms from different subspecies of Apis mellifera (Hymenoptera: Apidae) - Brochetto-Braga, Márcia Regina [UNESP]; Marques de Lima, Paulo Renato [UNESP]; Chaud-Netto, José [UNESP]; Arab, Alberto [UNESP]; Pereira Da Silva, Giselly [UNESP]; Cursino-Santos, Jeny Rachid (My University, 2005)
The enzymatic variability was analyzed in venom extracts from bees reared in different colonies of the Africanized, A. m. ligustica and A. m. carnica subspecies. The implications of this variation focused on the biochemistry differentiation and immunogenicity of these venoms. The results showed the existence of a huge variability among the subspecies as well as among the colonies for three out of the six tested components - hyaluronidase, acid phosphatase and proteases - suggesting the utilization of these features as possible biochemical markers. Furthermore, although not statistically significant, it was found that the Africanized bee venom presented slightly higher levels of protein content and esterase activity, when compared to the other subspecies. If the esterase plays a role in the pain intensity caused by the sting, as suggested elsewhere, this might suggest a reason for a bigger algogenicity of this venom in relation to that of European bees. On the other hand, A. m. ligustica bees presented the highest levels of proteolytic and acid phosphatase activities, whose functions are not enlightened in Hymenoptera venoms. The A. m. carnica workers presented the highest hyaluronidase and the lowest acid phosphatase activity levels. The extremely variable results among colonies of the same subspecies and among subspecies, for the tested venom components, justify the absence of correlation between allergic reactions and tests with pooled venom.
Keywords: Apis mellifera; Enzymatic variability; Honeybees; Subspecies; Venom; Apidae; Apoidea; Hymenoptera; Insecta